Biocompatibility evaluation of an antibiotic paste after pulpotomy in dogs - Glaucenira de Barros Bruno; Ana Paula Nunes Alves; Valdenice Aparecida Menezes; Maria Cristina Germano Maia; José Afonso Bruno; Glauce Socorro de Barros Viana (Universidade Estadual de Campinas, 2016)
The purpose of this study was to evaluate by histological analysis, the biocompatibility of an antibiotic paste following treatment of pulpotomies in dogs. Four male adult dogs were used and their mandibular and maxilar premolars and molars (PM3; PM4 ; M1 ; PM4 ; M1 ) of both sides were submitted to pulpotomies. The antibiotic paste (CTZ) was prepared with chloramphenicol, tetracycline, zinc oxide and eugenol. After 6, 8, 9 and 10 months post-pulpotomy the dogs were sacrificed. Histological analysis of the teeth revealed an intense inflammatory process in the coronal pulp at 6 months after pulpotomy, with inflammatory cells dispersed throughout the entire apical region in this period. This process became partially reduced at 8 and 9 months after pulpotomy, and totally disappeared by the end of the experiment, at 10 months. In conclusion, the endodontic treatment with this antibiotic paste seemed to be biocompatible under the present experimental conditions. However, further clinical studies are necessary to assure that this paste is safe for use in pulpotomies in children.